Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Performing the body: performing the text - Jones, Amelia..; Stephenson, Andrew; Jones, Amelia; Stephenson, Andrew (Routledge, 1999)
This book explores the new performativity in art theory and practice, examining ways of rethinking interpretive processes in visual culture. Since the 1960s, visual art practices - from body art to minimalism - have taken contemporary art outside the museum and gallery; by embracing theatricality and performance and exploding the boundaries set by traditional art criticism. The contributors argue that interpretation needs to be recognised as much more dynamic and contingent. Offering its own performance script, and embracing both canonical fine artists such as Manet, De Kooning and Jasper Johns, and performance artists such as Vito Acconci and Gunter Brus, this book offers radical re-readings of art works and points confidently towards new models for understanding art.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; premier cycle; périodes historiques; thématiques

Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Fields of play: Constructing an academic life - Richardson, Laurel W. (Rutgers University Press, 1997)
Comment les circonstances spécifiques dans lesquelles nous écrivons affectent-elles ce que nous écrivons ? Comment ce que nous écrivons affecte-t-il ce que nous devenons ? Comment pouvons-nous maintenir l'intégrité professionnelle et personnelle dans l'université d'aujourd'hui ? Dans une série d'écrits traditionnels et expérimentaux, aboutissement de dix années de travaux en cours, Laurel Richardson enregistre un parcours intellectuel, déplaçant les frontières et créant de nouvelles façons de lire et d'écrire. Appliquant l'imaginaire sociologique au processus d'écriture, elle relie sa vie à son travail. Profondément engageant, écrit de manière émouvante avec grâce, élégance et clarté, le livre stimule les lecteurs à situer leur propre écriture dans des contextes personnels, sociaux et politiques.
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; discipline; fem1000; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; théories féministes; écriture des femmes*; états-unis; études littéraires

Contre-voix : essais de critique au féminin - Saint-Martin, Lori (Nuit blanche, 1997)
Keywords: 1900-1999; 1990-1999; amériques; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; littérature; premier cycle; périodes historiques; québec; régions géographiques; thématiques; théories féministes; écriture des femmes*; études littéraires

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Creating worlds for my music to exist: How women composers of electroacoustic music make place for their voices - McCartney, Andra (Université York, 1994)
For this study, I have interviewed fourteen women composers of electroacoustic music in or near the three Canadian urban centres of Montreal, Toronto, and Vancouver. Montreal: Ciaire Pich6, Lucie Jasmin, Pascale Trudel, Monique Jean, Helen Hall and Kathy Kennedy; Toronto: Gayle Young, Sarah Peebles, Wende Bartley, Elma Miller, Ann Southam, and Carol Ann Weaver; Vancouver: Hildegard Westerkamp and Susan Frykberg. These interviews were all conducted between January and November of 1993. References to the development of electroacoustic music in Canada are sparse in the existing literature, both in general histories of electroacoustic music, and in histories of Canadian music. And even though there seem to be some areas of change (for instance, recent publications in Quebec), women composers are under-represented in writings and recorded collections of electroacoustic music in Canada. Chapter Two situates the work of women composers in the Canadian scene, discussing particularly the work of Norma Beecroft, Marcelle Desch§nes, Diana McIntosh, and Micheline Coulombe Saint-Marcoux. Chapter Three describes the metaphors, images and myths invoked in malestream discourses associated with electroacoustic music, in popular magazines, course texts and software. I investigate how my consultants’ language reflects and/or contests mainstream imagery, or how it might be framed by entirely different assumptions and experiences. Chapter Four is concerned with the institutional structures of electroacoustic music. I discuss how gendering exhibits itself in the division of labour in electroacoustic studio courses at universities, as well as in concert halls, conferences, and professional organizations. Excerpts from the interviews record my consultants experiences in these institutions, as students, teachers, and composers. In Chapter Five, I point out the variety of strategies that each composer uses to construct her identity within the world of electroacoustics. Each entry takes the form of a three or four page sketch, with quotes from the interview regarding the social environment, equipment choices, compositional styles, and particular pieces that my consultant discusses. Chapter Six discusses three pieces in detail: one by Susan Frykberg, Woman and House; one by Wende Bartley, A Silence Full of Sound; and one by Hildegard Westerkamp, Breathing Room. I focus on how each of the composers chooses to work with technology, and how her culturally-constructed position as a woman affects her work. I describe how my consultants imagine other stories to tell, and other possible lived social relations. The conclusions in Chapter Seven, in addition to suggesting areas for future research, discuss three themes that run throughout the study: the idea of gender as performance, the doubleness of my consultants' responses to technology, and the importance of the linguistic and musical metaphors that they use.
https://ocul-yor.primo.exlibrisgroup.com/permalink/01OCUL_YOR/j50f41/cdi_proquest_journals_304118103 Accès par ProQuest
Keywords: 1900-1999; 1990-1999; DIG; amériques; arts; canada; discipline; femmes* artistes; genre; montréal; musique; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; toronto; vancouver

Les discours féminins dans la littérature postmoderne au Québec - Koski, Raija Hellevi; Kells, Kathleen Elizabeth; Forsyth, Louise (The Edwin Mellen Press, 1993)
Ce volume est une collection soigneusement choisie de textes théoriques, poétiques, analytiques et critiques. Les voix des écrivai.e.s créatif.ves, des traducteurices professionnel.l.e.s et des universitaires offrent un éventail de perspectives sur les écrivaines québécoises contemporaines. À la lumière du postmodernisme, leurs textes proposent des lectures, des appréciations et des célébrations des écritures nouvelles et expérimentales au féminin québécois des trente dernières années. De plus, la bibliographie rassemble une mine d'informations sur ces écrivaines. En français.Les discours féminins . . . examiner la problématique et les fruits de la jonction, dans un contexte québécois, des deux grands mouvements sociaux, théoriques et littéraires d'aujourd'hui : le féminisme, et le postmodernisme. Le livre fait entendre les voix émouvantes et étonnantes de Louky Bersianik, Nicole Brossard, Susanne de Lotbinière-Harwood, Daphne Marlatt et France Théoret, et font lire les textes de quatorze spécialistes de la littérature québécoise dont Janet Paterson, Karen Gould, Louise Forsyth, Lori Saint-Martin. Les auteurices du livre nous offrent l'étude de l'oeuvre d'une ou de plusieurs écrivaines ou écrivains ; elles s'intéressent aux genres littéraires et à la traduction ; elles se penchent sur la question épineuse de la théorie dans l'émergence d'une littérature et d'une culture au féminin, et aussi sur les significations problématiques des termes "féminisme" et "postmodernisme". Ce livre représente un état présent de la plus grande pertinence et utilité, une exploration collective, sous plusieurs perspectives, d'une problématique complexe et tout à fait actuel.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; fem1000; littérature; postmodernisme; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Les voyages visionnaires de trois créatrices féministes-matristiques: Emily Carr, Jovette Marchessault et Gloria Orenstein - Orenstein, Gloria F. (Voix et Images, 1991)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; chamane; discipline; littérature; périodes historiques; ressource en ligne; théâtre; écoféminisme; études littéraires

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Section: 171 pages
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires